The factors that affect halal food and food products awareness and different challenges: An overview - Ali, Muhammad Qasim; Noormazlinah, Ahmad (Lembaga Pemasaran Pertanian Persekutuan (FAMA), 2023)
The growing concern about food and drink safety, hygiene, and quality has increased interest in halal products worldwide. These products, prepared according to Islamic dietary laws, are becoming more acceptable to Muslim consumers and those of other religions. This study examines the challenges faced by Malaysia in implementing halal food and food products. Despite some consumer skepticism about halal certifications, the industry has found that such certifications can be a helpful marketing tool for businesses. The study calls for cooperation between the private and public sectors to overcome these challenges. The study looks at the sources of Muslim knowledge consumers have about halal food and products. The results show that halal certification and awareness positively impact purchase intentions for halal food products. The study also provides a framework for examining factors that affect the integrity of the halal food supply chain and halal Islamic marketing, such as traceability, asset quality, quality assurance, and trust and commitment. The study also notes that halal and Islamic marketing is not limited to food but includes other product categories such as medicine, cosmetics, fashion, education, and entertainment. The study finds that Knowledge, halal certification, and Religiosity all play a role in shaping the halal awareness of business people.